Productivity of Eugenol from Clove (Syzygium aromaticum L.) Under Different Light and Soil Water Conditions - Adi Setiawan; Satoshi Ito; Yasushi Mitsuda; Ryoko Hirata; Kiwamu Yamagishi; Yasa Palaguna Umar; Ichiro Kamei (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
We examined the effect of watering and shading treatments on eugenol productivity of clove seedlings in order to provide the information of the suitable site conditions for eugenol production. After a six-month experiment growing clove seedlings under twelve treatments (3 shading treatments (0%, 60% and 80%) x 4 watering treatments (1.0, 0.75, 0.5 and 0.25 l/m2/day), the total leaf mass per tree (LM), the eugenol content per unit leaf mass (EL) and the eugenol yield per tree (EY) were measured and compared between treatments. As the results, the low watering rates reduced LM slightly; however, this effect was counteracted by the drastically increased EL under the same conditions, resulting in the highest EY in the least watered treatment (0.25 l/m2/day). Heavy shading consistently reduced LM and EL, resulting in the lowest LY under the 80% shading treatment. The relatively dryer site condition where moderate water stress is likely to occur is more suitable for planting clove trees from the aspect of the for long-term high productivity of eugenol, and that the high tree density which may cause a severe competition and a heavy mutual shading among clove trees should be avoided to maintain long term high productivity.